Immunomodulatory effects and mechanisms of the extracts and secondary compounds of Zingiber and Alpinia species: a review - Yuandani; Yuandani; Ibrahim Jantan; Md. Areeful Haque; Ade Sri Rohani; Sony Eka Nugraha; Emil Salim; Abdi Wira Septama; Nur Aira Juwita; Nur Aini Khairunnisa; Halimah Raina Nasution; Dinda Sari Utami; et al. (Frontiers Media S.A., 2023)
Zingiber and Alpinia species (family: Zingiberaceae) are popularly used in food as spices and flavoring agents and in ethnomedicine to heal numerous diseases, including immune-related disorders. However, their ethnomedicinal uses have not been sufficiently supported by scientific investigations. Numerous studies on the modulating effects of plants and their bioactive compounds on the different steps of the immune system have been documented. This review aimed to highlight up-to-date research findings and critically analyze the modulatory effects and mechanisms of the extracts and secondary compounds of several Zingiber and Alpinia species, namely, Zingiber officinale Roscoe, Z. cassumunar Roxb., Z. zerumbet (L.) Roscoe ex Sm., Alpinia galanga Linn., A. conchigera Griff, A. katsumadai Hayata, A. oxyphylla Miq., A. officinarum Hance, A. zerumbet (Pers.) Burtt. et Smith, and A. purpurata (Viell.) K. Schum. on the immune system, particularly via the inflammation-related signaling pathways. The immunomodulating activities of the crude extracts of the plants have been reported, but the constituents contributing to the activities have mostly not been identified. Among the extracts, Z. officinale extracts were the most investigated for their in vitro, in vivo, and clinical effects on the immune system. Among the bioactive metabolites, 6-, 8-, and 10-gingerols, 6-shogaol, and zerumbone from Zingiber species and cardamomin, 1'-acetoxychavicol acetate, yakuchinone, rutin, 1,8-cineole, and lectin from Alpinia species have demonstrated strong immunomodulating effects. More experimental studies using cell and animal models of immune-related disorders are necessary to further understand the underlying mechanisms, together with elaborate preclinical pharmacokinetics, pharmacodynamics, bioavailability, and toxicity studies. Many of these extracts and secondary metabolites are potential candidates for clinical development in immunomodulating agents or functional foods to prevent and treat chronic inflammatory disorders.